2016
DOI: 10.1016/j.mayocp.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Accumulation of Multimorbidity After Bilateral Oophorectomy: A Population-Based Cohort Study

Abstract: Objective To study the association between bilateral oophorectomy and the rate of accumulation of multimorbidity. Patients and Methods In this historical cohort study, the Rochester Epidemiology Project records-linkage system was used to identify all premenopausal women who underwent bilateral oophorectomy before age 50 years between January 1, 1988, and December 31, 2007, in Olmsted County, Minnesota. Each woman was randomly matched to a referent woman born in the same year (± 1 year) who had not undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
194
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 174 publications
(207 citation statements)
references
References 47 publications
8
194
1
Order By: Relevance
“…In addition to inaccurate understanding of their own OC risk estimates, genuine ambiguity regarding the long-term non-oncologic sequelae of RRSO in high-risk women compounds the complexity of the decision-making process. Among women at population risk of OC, large observational studies have shown conflicting results in terms of cardiovascular disease and overall mortality associated with bilateral salpingo-oophorectomy among women undergoing hysterectomy for benign indications [3840]; however, the effects of RRSO on non-oncologic morbidity in high-risk women is unclear and the benefits of OCS remain unproven. While these uncertainties, ambiguities and limitations cannot be fully eliminated at present, their existence warrants thoughtful discussion as patients weigh their management options.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inaccurate understanding of their own OC risk estimates, genuine ambiguity regarding the long-term non-oncologic sequelae of RRSO in high-risk women compounds the complexity of the decision-making process. Among women at population risk of OC, large observational studies have shown conflicting results in terms of cardiovascular disease and overall mortality associated with bilateral salpingo-oophorectomy among women undergoing hysterectomy for benign indications [3840]; however, the effects of RRSO on non-oncologic morbidity in high-risk women is unclear and the benefits of OCS remain unproven. While these uncertainties, ambiguities and limitations cannot be fully eliminated at present, their existence warrants thoughtful discussion as patients weigh their management options.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of accelerated aging comes from both biological markers (epigenetic clock) and from clinical measures (accelerated accumulation of multimorbidity). 5,6 …”
mentioning
confidence: 99%
“…The clinical recommendation should be simple and clear: In the absence of a documented high-risk genetic variant predisposing to ovarian cancer (eg, BRCA mutations), bilateral oophorectomy before the age of 50 years (or before menopause) is never to be considered and should not be offered as an option to women. 5,6 The possible alternative strategy of salpingectomy with ovarian conservation remains to be tested scientifically.…”
mentioning
confidence: 99%
“…Interestingly, these effects were reduced by initiating estrogen only MHT at time of oophorectomy and continuing to age 51 or 52 to coincide with natural menopause. These observations argue for MHT as close to the onset of hormone deficiency as possible for cardiovascular, bone, and nervous system protection …”
Section: Mht For Women With Iatrogenic Menopausementioning
confidence: 95%